An Electrochemical Assay for Monitoring Differentiation of the Osteoblastic Cell Line (MBA‐15) on the Sensor Chip. Issue 6 (24th March 2015) - Yildirim‐Semerci, Cigdem; Benayahu, Dafna; Adamovski, Miriam; Wollenberger, Ulla
Abstract An electrochemical assay for the indication of the activity of the cell bound differentiation marker alkaline phosphatase (ALP) is proposed using voltammetry on an in‐vitro cell culture. The basis of the assay is cultivation of cells on gold microelectrodes in wells of a microplate, catalytic hydrolysis of p‐aminophenyl phosphate by ALP and indication of p‐aminophenol oxidation by square wave voltammetry (SWV) with the sensors onto which the cells attached. The morphology of the bone marrow stromal cell line (MBA‐15) on the electrode surface was investigated and it exhibited in vitro osteogenic characteristics. Since ALP is expressed on the cell surface in early differentiation stage of osteoblastic cells, its activity was followed after different culture times over a period of 144 h by recording repetitive voltammograms at different time points upon addition of the substrate p‐aminophenyl phosphate. The ALP activity was estimated from the signal increase related to formation rate of p‐aminophenol and the number of cells. The highest value was measured at 120 h, when the cells reached confluence. The results of the electrochemical activity assay are consistent with the colorimetric acquired value from p‐nitrophenol formation rate.